2014
DOI: 10.1103/physrevb.89.115111
|View full text |Cite
|
Sign up to set email alerts
|

Longer-range lattice anisotropy strongly competing with spin-orbit interactions in pyrochlore iridates

Abstract: In the search for topological phases in correlated electron systems, materials with 5d transitionmetal ions, in particular, the iridium-based pyrochlores A2Ir2O7, provide fertile grounds. Several novel topological states have been predicted but the actual realization of such states is believed to critically depend on the strength of local potentials arising from distortions of the IrO6 cages. We test this hypothesis by measuring with resonant inelastic x-ray scattering the electronic level splittings in the A=… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
84
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 59 publications
10
84
0
Order By: Relevance
“…Therefore, in analogy to Ir L 3 -edge RIXS, we assign this transition to the excitation of the hole from the j eff = 1 2 ground state to the j eff = 3 2 band. In a single ion picture [5][6][7][8][9] the energy cost for this transition is 3ζ /2, from which the value of the spin-orbit coupling constant ζ is estimated to be 0.43 eV. This value remarkably agrees with the estimate of the spin-orbit coupling in Ba 2 IrO 4 (ζ = 0.42 eV) given in [14], based on the Ir L 2 and L 3 XAS branching ratio.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, in analogy to Ir L 3 -edge RIXS, we assign this transition to the excitation of the hole from the j eff = 1 2 ground state to the j eff = 3 2 band. In a single ion picture [5][6][7][8][9] the energy cost for this transition is 3ζ /2, from which the value of the spin-orbit coupling constant ζ is estimated to be 0.43 eV. This value remarkably agrees with the estimate of the spin-orbit coupling in Ba 2 IrO 4 (ζ = 0.42 eV) given in [14], based on the Ir L 2 and L 3 XAS branching ratio.…”
supporting
confidence: 81%
“…Whether or not the insulating behavior of Ba 2 IrO 4 can be explained within the framework of the j eff = 1 2 model is therefore unclear. Valuable insight into the physics of Sr 2 IrO 4 and related materials can be obtained within the frame of a single-ion model, in which 5d e g states are neglected and one hole fills the t 2g states, which are subject to tetragonal crystal field splitting ( ) and spin-orbit coupling (ζ ) [5][6][7][8]. For magnetic moments oriented along the (110) direction, the ground state * marco.moretti@esrf.fr wave function is written as [9] |0,− = C 0 (|xy,…”
mentioning
confidence: 99%
“…We will return to the low energy spectrum in more detail at the end of this section. In their quantum chemistry calculations, Hozoi et al 40 showed that the energies of the d-d excitations are quite similar for a variety of pyrochlore iridates (R = Sm, Eu, Lu, and Y). In particular, the non-cubic contribution to the crystal field splitting is quite significant in all four materials, as demonstrated by the large splitting between the two peaks associated with intra-t 2g transitions, E 1 ≈ 0.6 eV and E 2 ≈ 0.9 eV.…”
Section: Experimental Results: Excitationsmentioning
confidence: 99%
“…This is followed by three strong inelastic features: two sharp low energy excitations around 0.6-1 eV (E 1 and E 2 ) and an extremely broad high energy excitation around 2.5-5 eV (E 3 ). Quantum chemistry calculations 40 have shown that E 1 and E 2 arise from d-d excitations within the t 2g manifold, while E 3 arises from transitions between the t 2g and e g bands. We will demonstrate that there is also a fourth inelastic feature, which can be observed as a small shoulder on the right-hand side of the elastic peak.…”
Section: Experimental Results: Excitationsmentioning
confidence: 99%
“…Additional effects of SOC include XY anisotropy [11,12], locking of the magnetic moment to the correlated rotation of oxygen octahedra in Sr 2 IrO 4 [13], anisotropic dimer excitations in Sr 3 Ir 2 O 7 [14], and Kitaev-type magnetic interactions in Na 2 IrO 3 [15]. Structural distortions from the ideal octahedral environment have been observed in the pyrochlore family of the type R 2 Ir 2 O 7 (R =rare earth) where trigonal compression induces a reconstruction of energy levels [16,17].…”
mentioning
confidence: 99%